RHETORIC OF BINARIES ANTAGONISM IN CONSTRUCTING THE SOCIOLOGICAL NARRATIVE A NOVEL WHY YOU HATE REMARK AS A MODEL - Dr. Suad Badeea Muttai (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Opposites are one of the mechanisms for producing narrative discourse. In relation to the transformations made by the creator or narrator, and opposing changes in (title, character, event, space time). This study began from the inner world of the text (the dualities), and linked it to his concept of reality, or seeing the world in the novel (Why do you hate observation?) By Muhammad Alwan Jabr, which was based on the theme of love and war. Which, through its events, chronicles a society based on disparity. As a novel n why do you hate Remarque? It carries with it sociological themes that represent the difficult stages that Iraq went through with all its variables, which led to the depletion of the people's energy in wars that negatively affected the structure of Iraqi society, and then the contradiction had a suggestive effect on production. The meaning of the text by blending style with rhetoric and narrative domain Abd al-Qaher al-Jarjani says: "Things increase according to the evidence of opposites."